Cartas de amor en la Argentina peronista: construcciones epistolares del sí mismo, del sentimiento y del lazo político populista - Omar Acha (Centre de Recherches sur les Mondes Américains, 2007)
This study shows the relevance of letter-writing practices for the links between popular culture and populist identifications in the Argentinean politics of the mid-20th century. Love letter writing illustrates the development of a vast communicative knowledge where we can note the ego (or the self) constructions that were culturally useful to the spreading of models of peronist identification. In fact, as in everyday experience, Peronism love letters were decisive for the functional link between popular social demands, affection and identification. All of them were part of the legitimacy of peronist order and the persistence of its sentimental mythology.